Liberal juspolitical thinking: developments of the philosophy of Hayek and Nozick and the right of housing - Andrade, Eric Santos; Mota, Maurício Jorge Pereira da (REVISTA QUAESTIO IURIS, 2021)
It deals with an analytical-critical work that intends to question the presuppositions of the liberal vision, in particular that of Friedrich Hayek and Robert Nozick, in relation to social rights as sources of protection for individual freedom. Norberto Bobbio’s understanding is developed, which links the idea of Human Rights to the abstraction and universalization of fundamental values which, in turn, are nothing more than the redefinition of the classification of rights in generations. It is intended to discuss to what extent it will be up to the State to pursue social rights as a right, policy or provision of services, and if in fact we are talking about a competence that delegitimizes the state apparatus. To this end, a critical analysis of the liberal foundations on the right to housing and its perspective in Brazil will be built, especially under the reading of the Land Regularization Law (Act nº. 13.465 of 2017).